PEMAHAMAN DASAR PENDIDIKAN INKLUSI TERHADAP PARA GURU DI PONDOK MODERN BAITUL BIRRI - Alfian; Meiyanti Nurchaerani (CV. Multi Kreasi Media, 2022)
Basic understanding of inclusive education, especially for teachers at Pondok Modern Darul Birri. This must be supported by the teachers' understanding of inclusive education, which is relatively many who do not understand what inclusive education is. Based on this statement, our community service team focuses on community service to increase understanding of inclusive education. From the community service program, it is hoped that it can be useful for teachers in educating students, especially those with special needs in the modern darrul birri cottage. During the teaching activities at Pondok Modern Darul Birri, the principal and teachers work together to improve the quality of education.